The extent to which teachers of the basic stage in southern Badia education schools possess classroom management skills and their relationship to learning outcomes and social relationships between students - Alrawadieh, Khaled Haroun (Journal of Educational and Psychological Sciences, 2020)
The aim of this study is to reveal the extent to which the teachers of the basic stage in the southern Badia schools have classroom management skills and their relation to learning outcomes and social relations among students. To achieve the objective of the study, the researcher used the descriptive analytical method, where a tool was developed to achieve the objectives of the study, which included (70) paragraphs, divided into four sections. Applied to astratified random sample, the study sample size was 130)The results of the study showed that the basic stage teachers in the Southern Badia Directorate of Education possessed high classroom management skills, where the field of classroom environment ranked first with a very high grade. The rest of the four areas were: administrative skills, classroom problem solving, technical skills, and knowledge structure. And scientific classroom management, with high appreciation.It also showed that there are no statistically significant differences in the extent to which teachers possess the skills of classroom management attributable to variables: sex, sex of school, and number of years of experience. It showed a strong and statistically significant correlation between the total grade of classroom management skills, social relations among students, and learning outcomes based on comparisons of correlation coefficients, and the associated significance level values, which reached between classroom management and social relations between students. (0.40), between classroom management skills, and learning outcomes which reached (0.75) with no significant relationship between classroom environment and social relations where the correlation coefficient was (0.09), with a strong relationship between the classroom environment and learning outcomes where the correlation coefficient was (0.47). In the light of the results were Provide a number of recommendations and proposals, the most important of which is to maintain the high range of possession of classroom management skills.
Keywords: Basic Stage; Effective Classroom Management; Educational Outputs; Social Relations; Southern Badia